Cancer Stem Cells, MicroRNAs & Therapeutic strategies including Stem Cell Microparticles - Prokopi, Marianna; Pitsillides, Costas; Kapnisis, Konstantinos; Anayiotos, Andreas; Epenetos, Agamemnon; Kousparou, Christina (My University, 2014)
Introduction: In recent years, the cancer stem cell (CSC) model has been suggested to explain the functional heterogeneity and the carcinogenesis process of cancer. CSCs have the ability to initiate and sustain tumor growth, metastasis and resistance to therapy. MicroRNAs (miRNAs) are small non-coding RNA molecules, which function in transcriptional and post-transcriptional regulation of gene expression. Aberrant expression of miRNAs has been implicated in numerous diseases including some if not all cancer types. Recent findings suggest that miRNAs could be involved in maintaining and regulating the stemness of CSCs. Therefore, miRNAs have been proposed as attractive targets for therapy and miRNA-related therapeutic strategies are under investigation. However, systemic delivery of miRNAs faces its own set of limitations because miRNAs may be degraded in the blood by enzymes such as RNases and excreted by the kidneys. In this work we propose a novel system for therapeutic miRNA delivery applicable for both local and systemic administration with the use of umbilical cord mesenchymal stem cell (MSC) microparticles (MPs). Methodology: MSCs were isolated from the Wharton’s jelly of human umbilical cords. The MSC cultures were subjected to stress conditions, leading to the formation of MPs (secreted membrane vehicles <1μm) which were harvested and characterized by SEM, PCR, FACS and Fluorescence Microscopy. Breast (MDA-MB231 & MCF-7), colon (RKO & HT-29) and ovarian adenocarcinoma (SKOV3) cell lines were then exposed to MPs. The response to treatment was evaluated by cell morphology, proliferation, migration, gene expression and apoptosis. Furthermore, the therapeutic potential of MPs was tested in vivo in xenograft tumor mouse models. Innovative imaging modalities such as in vivo flow cytometry and whole body fluorescence-bioluminescence were employed to dynamically investigate the biodistribution and homing kinetics of MPs in mice. Results: In vitro experiments confirmed that MSC-derived MPs can be internalised by the various cancer cell lines and induce a biological effect as evidenced by membrane damage, cell shrinkage and blebbing in the recipient cell. Significantly, there was evidence that MPs induce apoptosis, inhibit cell proliferation and mediate tumor growth attenuation in a dose/time-dependent manner. The proapoptotic and anti-migrating effects of MPs in cancer cells were almost completely abrogated by RNase treatment before administration to cultures. Preliminary in vivo studies demonstrated that we were able to monitor and quantify fluorescently labelled MPs in circulation and to detect and image the biodistribution and incorporation in cells and organs in healthy and tumor-bearing mice. Conclusion: MSC-derived MPs containing miRNAs possess tumor inhibitory properties both in vitro and in vivo. Administration of MPs after RNase treatment induces the loss of anti-cancer properties suggesting a horizontal transfer of small RNAs from MPs to cancer cells. MPs formulated to contain specific miRNAs, could affect the action of genes associated with carcinogenesis, neovascularization, metastasis and other cancer characteristics leading to therapeutic benefit.
Keywords: Cancer stem cell; MicroRNAs; Therapeutic miRNA